Robust Estimation of Jitter in Pathological Voices - Agüero, Pablo Daniel (2010)
Acoustical analysis of speech using computers has reached an important development in the latest years. The subjective evaluation of a clinician is complemented with an objective measure of relevant parameters of voice. Praat, MDVP and SAV are some examples of software for speech analysis. In this paper we describe an algorithm for the estimation of the fundamental frequency that considers the non-periodic nature of the speech signal under analysis. The experiments show that the use of these estimated f0 values reduces the errors in perturbation measures of f0, compared to the errors of other state-of-the-art speech analysis softwares, such as Praat and MDVP.